We choose exact sciences? - Gesevičienė, Vilma; Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2014)
The article overviews the priorities and motives of choosing the subjects of exact sciences by senior form learners of the Lithuanian secondary schools and gymnasiums as well as compliance with future learners plans of professional activity and studies.